Volume-regulated anion channels conduct ATP in undifferentiated mammary cells and promote tumorigenesis in xenograft nude mouse - Furuya, Kishio; Hirata, Hiroaki; Kobayashi, Takeshi; Ishiguro, Hiroshi; Sokabe, Masahiro (Frontiers in Cell and Developmental Biology, 2025)
The high interstitial ATP concentration in the cancer microenvironment is a major source of adenosine, which acts as a strong immune suppressor. However, the source of ATP release has not been elucidated. We measured ATP release during hypotonic stress using a real-time ATP luminescence imaging system in breast cell lines and in primary cultured mammary cells. In breast cell lines, ATP was released with a slowly rising diffuse pattern, whereas in primary cultured cells, ATP was intermittently released with transient-sharp peaks. The diffuse ATP release pattern changed to a transient-sharp pattern by cholera toxin treatment and the reverse change was induced by transforming growth factor (TGF) β treatment. DCPIB, an inhibitor of volume-regulated anion channels (VRACs), suppressed the diffuse pattern. The inflammatory mediator sphingosine-1-phosphate (S1P) induced a diffuse ATP release pattern isovolumetrically. Knockdown of the A isoform of leucine-rich repeat-containing protein 8 (LRRC8A), the essential molecular entity of VRACs, using shRNA suppressed the diffuse pattern. In the nude mouse xenograft model, LRRC8A knockdown suppressed the tumorigenesis of subcutaneously implanted breast cancer cells. These results suggest that abundantly expressed VRACs are a conduit of ATP release in undifferentiated cells, including cancer cells.